2022
DOI: 10.1155/2022/9954404
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Shade on Agro-Morphological Parameters and Weed Flora of Saffron (Crocus sativus L.) Cultivation in the Semiarid Zone of Eastern Morocco

Abstract: Saffron (Crocus sativus) has been an important medicinal plant since ancient times. This study aimed to seek the optimal light intensity for saffron growth by quantifying the effects of different shade levels on yield, vegetative growth, and weed development in the eastern region of Morocco. The plants were grown for 24 months in full sun (control) and 30%, 50%, and 70% shade. Overall, the results showed that shade positively affected the yield and vegetative growth parameters of saffron plants, with the highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…Weeds are controlled by mechanical, hand weeding, or chemical methods. Although mechanical and hand weeding are effective and environmentally friendly, they are time-consuming and costly [14,15]. Hosseini-Evari et al [16] revealed that a combination of herbicide (Metribuzin) with the mulch method can be useful for weed management in saffron.…”
Section: Introductionmentioning
confidence: 99%
“…Weeds are controlled by mechanical, hand weeding, or chemical methods. Although mechanical and hand weeding are effective and environmentally friendly, they are time-consuming and costly [14,15]. Hosseini-Evari et al [16] revealed that a combination of herbicide (Metribuzin) with the mulch method can be useful for weed management in saffron.…”
Section: Introductionmentioning
confidence: 99%
“…Saffron is grown on different types of welldrained soils with a pH range from neutral to slightly alkaline (Ghanbari et al, 2019). According to the results of research (Mzabri et al, 2022), the productivity of the receptacles is affected by illumination: the highest productivity is observed at 30% shading. The culture is resistant to low and high temperatures and withstands their range from -22 to 40°C (Siney et al, 2020).…”
Section: Introductionmentioning
confidence: 99%